Konsep Kafa’ah pada Perkawinan Syarifah Di Desa Pambusuang Kabupaten Polewali Mandar - Mayanti; Andi Jusran Kasim (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2023)
This study uses a qualitative research method with empirical legal research located in Pambusuang, Balanipa, Polewali Mandar. It is conducted by using a normative theological and sociological research approach. The primary data sources are several Syarifah women and Habib. The study reveals that the Syarifah women's marriage system is not significantly different from the women's marriage system in general in Pambusuang, namely using the traditional Mandar procession, however, there are few differences are found. First, Syarifah women's marriage tends to focus on nasab (lineage) at the matchmaking process or at the proposal process so that the marriage is arranged, they do not apply several kufu' concepts (compability) in choosing a partner, and some of them even choose not to marry. Second, at the metindor process in Syarifahs' Wedding (arrival of the groom), the groom should attend the syarifahs' place by riding a horse. Third, the groom has to wear white to carry out the Ijab kabul . Regarding the first result, the concept of kafâ`ah for Syarifah women in achieving sakinah mawaddah warahmah marriage cannot be separated from the combination of several kufu’ concepts, such as religion, lineage, work, and wealth. However, in their marriage, the concept of kufu' in terms of lineage and religion is the most important consideration when choosing a partner while the wealth and work aspect are tend to be ignored nowadays. The implication of the research is that there is an understanding that not only lineage of sayyid descent is a determinant in achieving a life of sakinah mawaddah warahmah for syarifah women in Pambusuang, but it is also necessary to grant rights to Syarifah women to choose their partner outside the lineage of sayyid rather than live unmarried because they are not from the same nasab (lineage).